2017
DOI: 10.1091/mbc.e16-10-0695
|View full text |Cite
|
Sign up to set email alerts
|

Wound-induced Ca2+wave propagates through a simple release and diffusion mechanism

Abstract: Establishment of a signaling gradient around a wound is initiated by a wave of calcium activation. Multiple mechanisms have been proposed to explain calcium propagation. This study shows that calcium activation is a result of the release of ATP from wounded cells followed by simple diffusion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 47 publications
7
28
0
Order By: Relevance
“…Given that the genes we probe are related to Ca 2+ signaling, we first extracted key features from time series of cytoplasmic Ca 2+ response measured with a calibrated GCaMP5 biosensor (Appendix Fig S2A). The live cell imaging of cytoplasmic Ca 2+ levels (Fig C) showed a highly heterogeneous response, qualitatively and quantitatively similar to previous work on Ca 2+ signaling in MCF10A cells where we observed a mixed population response with a wide range of response phenotypes (Yao et al , ; Handly & Wollman, ). We used a feature‐based representation of Ca 2+ response to represent cellular factors that we anticipate correlate with underlying cell state (Fig G and Appendix Fig S2).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Given that the genes we probe are related to Ca 2+ signaling, we first extracted key features from time series of cytoplasmic Ca 2+ response measured with a calibrated GCaMP5 biosensor (Appendix Fig S2A). The live cell imaging of cytoplasmic Ca 2+ levels (Fig C) showed a highly heterogeneous response, qualitatively and quantitatively similar to previous work on Ca 2+ signaling in MCF10A cells where we observed a mixed population response with a wide range of response phenotypes (Yao et al , ; Handly & Wollman, ). We used a feature‐based representation of Ca 2+ response to represent cellular factors that we anticipate correlate with underlying cell state (Fig G and Appendix Fig S2).…”
Section: Resultssupporting
confidence: 88%
“…We used sequential hybridization smFISH (MERFISH implementation) (Moffitt et al , ) that allowed us to accurately measure the expression of 150 genes in ~ 5000 single cells. Since expression covariance between genes from the same pathway is higher compared to genes that have distinct functions (Sigal et al , ; Stewart‐Ornstein et al , ), we focused on a single signaling network and biological function, Ca 2+ response to ATP in epithelial cells, and a biological response important to wound healing (Funaki et al , ; Handly et al , ; Handly & Wollman, ). The key advantage of Ca 2+ response is that the overall signaling response can be measured in < 15 min, a fast timescale that precludes any ATP‐induced changes in transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the genes we probe are related to Ca 2+ signaling we first extracted key features from time-series of cytoplasmic Ca 2+ response measured with a calibrated GCaMP5 biosensor (S2 A). The live cell imaging of cytoplasmic Ca 2+ levels ( Figure 2C) showed a highly heterogeneous response, qualitatively and quantitatively similar to previous work on Ca 2+ signaling in MCF10A cells where we observed a mixed population response with a wide range of response phenotypes (Handly and Wollman, 2017;Yao et al, 2016) . We used a feature-based representation of Ca 2+ response to represent cellular factors that we anticipate correlate with underlying cell state ( Figure 2G and S2).…”
Section: Resultssupporting
confidence: 87%
“…We used sequential hybridization smFISH (MERFISH implementation) ) that allowed us to accurately measure the expression of 150 genes in ~5000 single-cells. Since expression covariance between genes from the same pathway is higher compared to genes that have distinct functions (Sigal et al, 2006;Stewart-Ornstein et al, 2012) , we focused on a single signaling network and biological function, Ca 2+ response to ATP in epithelial cells, a biological response important to wound healing (Funaki et al, 2011;Handly et al, 2015;Handly and Wollman, 2017) .The key advantage of Ca 2+ response is that the overall signaling response can be measured in less than fifteen minutes, a fast timescale that precludes any ATP induced changes in transcription. Using the combined dataset we were able to separate the correlated and uncorrelated components using a simple multiple linear regression model guided by the changes in the covariance matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous treatment of ionomycin and the potent phosphatase inhibitor Okadaic acid, which inhibits protein phosphatase 1 upstream of YAP (39), led to a similar degree of cytoplasmic sequestration but with minimal recovery, suggesting that Ca² + drives phosphorylation of YAP followed by PP1-dependent dephosphorylation ( Supplementary Figure 2a). Previous reports have shown that the release of extracellular ATP may drive FCW at epithelial wound edge (40). Although addition of 10mM extracellular ATP induced a similar response as TG and ionomycin, we found there was a sharp dependence on local cellular density, with sparse cells responding minimally ( Supplementary Figure 2b).…”
supporting
confidence: 54%